Survival Analysis and Factors Associated with Pulmonary Tuberculosis - Zul Adhayani Arda; Sunarti Hanapi; Nur Hamdani Nur; Sabrina Nadjib Mohamad; Mohammad Amon (Pusat Pengembangan Teknologi Informasi dan Jurnal Universitas Muhammadiyah Palu, 2025)
Introduction: Analysed the survival rates of patients and factors associated with pulmonary tuberculosis at the Limboto Public Health Center, with particular attention to the role of hypertension as a predictor of treatment failure and its potential integration into TB treatment guidelines. Methods: The study represents retrospective cohort research conducted by collecting medical records of individual pulmonary tuberculosis patients at the Limboto Public Health Center. The research sample comprised 144 patients and was analysed using survival analysis methods, including the Kaplan-Meier and Cox Regression models. Result: Among a cohort of 144 pulmonary tuberculosis cases, 21 individuals (14.6%) encountered treatment failure, resulting in three fatalities. A Kaplan-Meier survival analysis unveiled marked disparities in the survival probabilities of pulmonary tuberculosis patients contingent on their hypertension status (p=0.000). In the Cox Regression analysis, the hazard ratio associated with hypertension in the context of treatment failure in pulmonary tuberculosis patients was determined to be HR= 10.216. These findings suggest the necessity of incorporating hypertension screening and management into existing TB care protocols. Conclusion: Evidence-based interventions should be implemented, particularly among patients with concomitant hypertension. Strengthening the integration of hypertension management into TB treatment guidelines may improve patient outcomes and reduce treatment failures.